Promoting students’ creativity At research universities in Malaysia - Afshari, M.; Ghavifekr, S.; Ayoufu, W. (2012)
Creativity is an important element in the development of educational organizations. Although many variables influence students’ creativity in universities, there is reason to suspect that leadership behaviours’ of lecturers represent a particularly powerful influence. In this study, we examined leadership behaviours contributing to enhancing students’ creativity. Findings of this study indicated that leadership behaviours of lectures such as idealized influence, intellectual stimulation, inspirational motivation, technical skills, and involvement may influence students’ creativity both directly and indirectly. Their leadership behaviours may nurture or stifle students’ creative potential. The implications of these findings for theory and practice are discussed.